Analisis Pemanfaatan Media Puzzle Dalam Meningkatkan Minat Belajar Siswa Pada Tema IV Berbagai Pekerjaan di Kelas IV SD - Halimsyah Rambe, Andina (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2023)
This research aims to find out the effectiveness of the use of puzzle media themes of various sub-theme work in increasing students' learning interest in grade IV B elementary school Amelia Tembung. The research methods used exist; ah qualitative research with case study methods. The object of this study was a class IV B student of Siti Amelia Elementary School which numbered 30 people with 15 male and 15 female. The data collection techniques used are observation, interview and documentation. The data analysis techniques used are by collecting data, clasification data, presenting data, inference and verification. The results showed that the use of puzzle media themes of various sub-theme work in increasing students' learning interest in grade IV B elementary school Amelia Tembung very interesting attention and spirit of students in following the learning even though it is in the last hour. Teachers engage students directly in learning and train students to work in teams to solve the problems provided. Learning using puzzle media can increase students' learning interest. This can be reviewed from the evaluation of indikators of increased learning interest